Veropa is pai d'égua: the hospitality and the flavors of the Ver-o-Peso market in Belém (PA) - Oliveira, Daniella Cristiane Santos (Universidade Federal do Rio de Janeiro, 2023)
Located on the banks of the Guamá River in Belém do Pará, the Ver-o-Peso market was founded in 1625 as a tax office. In the context of the emergence of urban centers, the open fairs can be considered a factor that contributes to the socioeconomic development of a particular location, as in the case of Ver-o-Peso, which over the years assumed a leading role in the lives of the people of Pará, who use it daily as a market and especially as one of the main tourist attractions of the capital of Pará. Considering this, the present article aims to understand the historical aspects of this place, as well as the hospitality relations that occur there, and to focus on the main point of the market's experience and commerce – the typical food – drawing parallels between them. To carry out this work, the bibliographical research and participant observation were used as methodology. As results, it is observed the duality between welcoming and hostility for both the local population and the tourist, arising from the daily experiences in such an important tourist spot for Belém.